Steadfast heart [large type] - Peterson, Tracie (Peterson, Tracie. Brides of Seattle, 2015)
Lenore Fulcher's deepest desire at the age of twenty is to find true love. However, her father wants to marry her off to James Rybus, one of his business partners. But the idea of marriage to a man seventeen years older is out of the question for Lenore. Kolbein Booth, a lawyer from Chicago, arrives in Seattle looking for his headstrong sister who he believes may have answered an advertisement for mail-order brides. Sick with worry, he storms the Madison Bridal School, demanding to see his sister, only to learn she isn't there. But Lenore Fulcher is, and something about her captures his attention.